System of governance and administration in the state of the Ottoman Algeria (1518-1830) - سحر ماهود محمد (College of Education for Women, 2019)
Algeria is one of the states that are important to the Ottoman state, because of its geographic location is important to the Mediterranean Sea, as well as the economic resources of the nature of its soil geography and climate,diverse, making it the focus of attention of the Ottomans, along with the van, which has increased the interest of the Ottomans in Algeriais the fall Andalusat the hands of the Spaniardsin1492, and force the Muslims to get out of them, and did not Only Europeans do it, butrushed to the prosecution of Muslims tothe coast of North Africa and seizing control of manyofits ports and cities, prompting the Ottoman state to go forth and back to the barn Muslims,Especially after hehad appealed to the Arabs of the Ottoman state, specifically Algeriawhosenttelegramsto the distress of the Sultans Osman, demanding rescued from Europe and omination. The increased interest in the Ottoman Empirein Algeria after the Call herbrothersmystic and Khairudd in, who supplied them with the Ottoman saiduntil they were able to imposetheir control over Algeriaand the establishment of Ottoman rule there, and then worked the Ottoman stateto find an administrative system fits with its system of governance, asdivided Algeriaon the provinces and place don top of each provincegovernor beconnected to the first rule of the city of Algiers. In this study, the focus was on how to enter Algeriaunder the authority of the Ottomans, and what are the administrative proceduresfollowed by the Ottoman Empireto rule the state of Algeria, which has continue dsince1518, when it was established rule Baklrbakah; that under went Algeria French rulein 1830AD.